Partnership and public administration: conceptual and practical considerations - Kernaghan Kenneth
In recent years, there has been a proliferation of partnerships involving public organizations. The use of partnerships has evolved from an ad hoc response to particular problems to a general approach to problem-solving and to improving the efficiency, effectivencess, and responsiveness of public organizations. Partnerships are also used to empower individuals, groups and organisation outdsiide government by enabling them to make a geniune contribution to their decisions affecting them. It is important, therefore, to explain the meaning and types of partnership, to examine their purposes, benefits, and participants, and to assess their political implications. In-depth evaluative studies of partnerships are s
Keywords: Personnel-Employee Relations; Partnership; Organisation; Management; Employee Relations; Public Administration